Moderasi Hukum Islam dalam Pemikiran Ahmad Hasyim Muzadi - Moh Dahlan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
This study aims to examine the paradigm of moderate ijtihad by Ahmad Hasyim Muzadi and moderation discourse of Islamic law that was built by Ahmad Hasyim Muzadi. This study used the approach is the thought of Milton K. Munitz. This study showed that the paradigm of moderate ijtihad that built by Ahmad Hasyim Muzadi should not be based on the texts of Islamic law only, but also to be devout and clear thinking, honest, and sincere. In this way, the moderation  of Islamic law discourse that resulted will bear the legal system that is inclusive and accommodated to the dynamics of human life. Islamic legal discourse that has a balance and fairness in enforcement at the empirical level